PEMBELAJARAN ALQURAN HADIS DI MAN PAGAR ALAM - Defit Roly (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2016)
Abstract: This study aims to determine the learning of Alquran and Hadits in Religious Senior High School students of Pagaralam. The results of this study used for several strategies, namely balancing the classical and individual learning approach which are arranged i practically so it is easy to be learned, emphasizing the ability of learners to be able to read the Qur‟an in tartil, using variations of the recitations theme of the Qur‟an so that the reading is not boring, using the system of sima’an (listening) so the learners are able to justify or correct the Qur‟an recitation of other learners. The learning process is also done by creating lesson plans by the teacher in charge of teaching the Qur‟an. By providing matriculation, the students are expected to know in advance before they get a Qur‟an lesson in the learning process so that they know more about what will be learned. With more familiar with what will be learned, the students get a basic overview of the entire subject matter provided, organizing study groups, and the development through extracurricular activities. Internal factors which may affect the learning of the Qur‟an is the willingness of students to learn, students‟ interest towards learning the Qur‟an is not maximized and the lack of motivation of students to learn the Qur‟an further. External factors are the parents and families who are very influential on students‟ ability to read the Qur‟an. Among families (parents) and school (teachers) has a role, influence and responsibility for the success of the Qur‟an education at Religious Senior High School of Pagaralam.